2023
DOI: 10.3390/ijerph20065031
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination and Stress: A Conceptual Review of Why Context Matters

Abstract: Research over the past two decades has continued to highlight the robust associations between procrastination and stress across multiple populations and contexts. Despite this burgeoning evidence base and theory linking procrastination to higher levels of stress, as well as the reverse, the role of context in this potentially dynamic association has received relatively little attention. In this conceptual review I argue that from a mood regulation perspective of procrastination, stressful contexts necessarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 112 publications
1
4
0
Order By: Relevance
“…For instance, GERD was more prevalent among old age participants, IBD was more common among age groups 40-49 years, and psychological disorders among younger age participants with recorded statistical significance (P value =.001). It is intriguing that despite significant differences in population genetic structures, lifestyles, and nutritional aspects at different geographic regions, this pattern remains similar to reports from global communities including Korea [30], Palestine [31], USA [32 33], UK [34], China [35]. This common syndrome is consistent with the widely established scientific notion that the gut nerve cells we're born with are the same ones we die with.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For instance, GERD was more prevalent among old age participants, IBD was more common among age groups 40-49 years, and psychological disorders among younger age participants with recorded statistical significance (P value =.001). It is intriguing that despite significant differences in population genetic structures, lifestyles, and nutritional aspects at different geographic regions, this pattern remains similar to reports from global communities including Korea [30], Palestine [31], USA [32 33], UK [34], China [35]. This common syndrome is consistent with the widely established scientific notion that the gut nerve cells we're born with are the same ones we die with.…”
Section: Discussionsupporting
confidence: 82%
“…Among the demographic factors associated with the disorders showed that female respondents were more likely than male counterparts with 72.4%(n=1496) compared to 27.6% males (n=571). Age groups indicated that 66%(n=1364) were young between 18-29 years while only 13% and 12.5% were (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and 40-49), respectively. Seniors aged 50-59 and over 60 were the least frequent responders at 6% and 2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Stigmatisation in AD involves both stigmatisation by others and self-stigmatisation. Stigma, esteem, efficacy, depression, and activation are inter-related and any therapy should address all of these; otherwise, low motivation and hopelessness would deter any possibility of therapeutic progress [ 66 , 67 , 68 ].…”
Section: Mental Health Conditions Associated With Admentioning
confidence: 99%
“…The direct impact of procrastination and IWB According to self-determination theory, employees who possess intrinsic motivation are inherently inclined to participate in a given task due to the gratification and rewards it provides (Ryan & Deci, 2000). Even employees, who are intrinsically driven, may put off completing a task if it seems too hard or stressful (Sirois, 2023) or if they find something else more intriguing (Ferrari et al, 1995). A number of scholars are of view that procrastination involves intentionally putting off important tasks until later, even while the person knows that putting them off would hurt them and people around them (Steel, 2007;Sirois & Pychyl, 2013).…”
Section: The Direct Impact Of Polychronicity and Procrastinationmentioning
confidence: 99%